Rupiah Depreciation and the Competitiveness of Indonesian Halal Exports: A Critical Review from the Perspective of Islamic International Economics - Yunita Dalimunthe; Inayatul Widad Nasution; yusrizal; M Ridwan (Yayasan Darussalam Bengkulu, 2026)
Background: The depreciation of the rupiah exchange rate is an economic phenomenon that can impact the export competitiveness of Indonesian halal products. While the rupiah's depreciation has the potential to increase product price competitiveness in the international market, it can also increase production costs due to the industry's dependence on imported raw materials and technology. This study aims to analyze the impact of rupiah depreciation on the competitiveness of Indonesian halal exports and examine it from an Islamic international economic perspective. Method: This research uses a qualitative approach with a narrative literature review method. Data was collected from scientific articles, academic books, official institutional reports, and various publications relevant to exchange rates, export competitiveness, halal industry, and Islamic economics. The analysis was carried out using thematic analysis techniques through a process of identification, categorization and synthesis of previous research findings. Results: Hasil penelitian menunjukkan bahwa depresiasi rupiah dapat meningkatkan daya saing ekspor halal Indonesia melalui keunggulan harga di pasar internasional. Namun, dampak positif tersebut dibatasi oleh kenaikan biaya impor dan faktor non-harga, seperti kualitas produk, sertifikasi halal, kapasitas produksi, dan akses pasar global. Dalam perspektif ekonomi internasional Islam, peningkatan ekspor halal harus mendukung prinsip maslahah, al-'adl, dan tawazun Conclusion: Conclusion: Rupiah depreciation can support the competitiveness of Indonesia’s halal exports, but its impact remains limited without improvements in product quality, halal certification, production capacity, and market access. Therefore, exchange rate depreciation should be viewed as a supporting factor rather than the primary driver of halal export competitiveness.